Evaluation of tungsten as divertor plasma-facing material: results from ion irradiation experiments and computer simulations. (11th June 2019) - Maya, P.N.; Sharma, P.; Satyaprasad, A.; Mukherjee, S.; Tyagi, A.K.; Vala, S.S.; Subhash, P.V.; Attri, A.; Kulriya, P.; Bajpai, P.K.; Raole, P.M.; Karki, V.; et al.
Abstract: The effect of the primary knock-on atom (PKA) spectrum in radiation damage and the subsequent defect structure formation and their impact in deuterium (D) trapping has been investigated using computer simulations and surrogate ion irradiation experiments. The neutron spectrum for an 'ITER-like' divertor shape and parameters has been generated using ATTILA and SPECTER codes to identify the relevant PKA energies. It has been observed that 10 MeV boron (B) produces a PKA spectrum similar to that obtained from a reactor-like neutron spectrum. Experiments have been carried out with ions of gold (Au), B, helium (He) and D with energies ranging from 0.1 MeV–80 MeV for a fluence range of ions m −2 – ions m −2, and distinctly different PKA spectra have been produced. While 80 MeV Au ions produced dense and small clusters of interstitial defects (<10 nm), B produced large dislocation loops up to 60 nm in size. At room temperature, the imprint of the cascade is well captured by the vacancies due to their low mobility, and the vacancy defects observed in Au and B irradiation showed significant differences. Molecular dynamics simulations show that at PKA energies exceeding 150 keV, the fragmentation of the cascades takes place, which tends to limit the size of individual defects in the case of 80 MeV Au irradiation. A mechanism based on the competitive capture of mobile interstitials has been proposed to explain the observed large dislocation loops as well as dislocation lines in different irradiation experiments.